Primary malignant melanoma of the oesophagus: case report and review of surgical pathology. - Stranks, G J (1991)
Primary malignant melanoma of the oesophagus is both a rare presentation for melanoma and a cause of oesophageal neoplasm. It accounts for less than 0.1% of all primary oesophageal neoplasms. It was first recognised as a primary tumour by de la Pava et al who showed the presence of melanocytes within oesophageal mucosa. This case report includes a review of the surgical pathology. Even though it is a rare lesion it must be considered as a cause of polypoidal oesophageal lesions as both its diagnosis and treatment can present problems. It is usually fatal within one year.